Insights into the Role of Helicobacter pylori Infection in Preeclampsia: From the Bench to the Bedside - Tersigni, Chiara; Franceschi, Francesco; Todros, Tullia; Cardaropoli, Simona; Scambia, Giovanni; Di Simone, Nicoletta (Frontiers in Immunology, 2014)
Preeclampsia (PE) is defined as a hypertensive and coagulative disorder affecting about 2–8% of all pregnancies and it is one of the main causes of maternal and fetal morbidity and mortality. Despite the great amount of studies run in this field, little is known about the precise pathogenic mechanisms behind PE. While endothelial and trophoblast dysfunctions, exaggerated inflammatory response and hypercoagulative state have been shown to play a key role in the occurrence of PE, the primary trigger is still unknown. One of the hypotheses is that some infectious agents may represent a trigger for PE onset. Consistently, higher seroprevalence of Helicobacter pylori (HP) infection, a Gram-negative bacterium with a specific tropism for human gastric mucosa, has been shown in women with PE. Even tighter association has been found between PE and infection with CagA (Cytotoxin-associated gene-A) -positive strains of HP. Recent in vitro studies have shown that anti-CagA antibodies cross-react with human trophoblast cells and determine a functional impairment in terms of cell invasiveness, thus, providing the first pathogenic model of HP infection-mediated placental damage. Since in the early process of implantation and placental development, trophoblast invasion of maternal decidua is a crucial step, the proposed autoimmune mechanism induced by HP infection, negatively interfering with the fetal side of the early developing placenta, may represent a mechanism explaining the higher seropositivity for HP infection among PE women. However, the contribution of HP infection to the pathogenesis of PE or to the worsening of its clinical presentation needs to be further investigated as well as the possible impact of pre-pregnacy screening and eradication of HP infection on the incidence of the syndrome.